Japanese Encephalitis Virus Upregulates the Expression of SOCS3 in Mouse Brain and Raw264.7 Cells - Xiangmin Li; Qiaoyan Zhu; Qishu Cao; Huanchun Chen; Ping Qian (Viruses, 2014)
Japanese encephalitis virus (JEV) is one of the pathogens that can invade the central nervous system, causing acute infection and inflammation of brain. SOCS3 protein plays a vital role in immune processes and inflammation of the central nervous system. In this study, Raw264.7 cells and suckling mice were infected with JEV, and SOCS3 expression was analyzed by the gene expression profile, semiquantitative RT-PCR, qRT-PCR, immunohistochemistry (IHC) and Western blot. Results indicated that 520 genes were found to be differentially expressed (fold change ≥ 2.0, p < 0.05) in total. The differentially regulated genes were involved in biological processes, such as stimulus response, biological regulation and immune system processes. JEV early infection could induce SOCS3 expression, upregulating both the mRNA and protein levels in Raw264.7 cells in a time-dependent manner. The SOCS3 expression was much lower in Raw264.7 cells infected with inactivated JEV than wild-type JEV. In vivo, SOCS3 protein was also found to upregulate the expression of mRNA and protein in JEV-infected mouse brain. Taken together, our data showed that JEV early infection could induce the upregulation of SOCS3 expression, both in vitro and in vivo, providing the basic theoretical foundation for future research on the invasion mechanism of JEV.